Pica Magz/Pica Fest: Creative Economy In Bali Subculture - Bastari, Rendy Pandita; Resmadi, Idhar; Utama, Jiwa (Universitas Negeri Semarang, 2022)
.Bali's creative economy in 2020 shows that 26.26% was dominated by music, 12.64% from performing arts, 8.29% from culinary, and 52.81% from other sub-sectors. By looking at the data, there are one sub-sector that is not quite as significant as the others and that is fashion. One subculture actor who is quite active in the local fashion industry is Pica, subdivided by Picamagz and Pica Fest. They are quite constant in holding subcultural events such as music shows and fashion festival. This proves that local fashion industry can give contribution and can also be supported by other industry. The purpose of this study is to analyze the social creative field of Picamagz and Pica Fest. The method used for this study is qualitative descriptive with the validation from interviews and observation. The result of this study shows that that the field of expression, production, dissemination and appreciation filled with active actors who holds their respective role.